Methodological approaches to the efficient functioning assessment of the modern upper structure track - E. N. Efimova; N. P. Vinogorov; A. A. Shiladzhyan; V. M. Koshelev; D. A. Valov; N. V. Kuznetsova (Вестник Научно-исследовательского института железнодорожного транспорта, 2022)
Introduction. The article covers the approaches to assessing the efficient functioning of the modern upper structure track and aims at developing these approaches in the process of using the track superstructure materials — rails, fasteners, sleepers, ballast — under given operating conditions.Materials and methods. The authors proposed methodological approaches for assessing the effective functioning of the modern upper structure track. These methods were based on the life cycle cost measurements of railway complex technical systems. The methodological approaches enable to consider the expenditures for the acquisition, possession and disposal of the upper structure track materials by discounting the cost indicators and the initial period value.Results. The authors present the results of test calculations for assessing the effective use of ZhBR-65PShM, ZhBR-65Sh, ARS-4, Vossloh W-30 rail fasteners types on a 12-kilometer nominal section of the continuous welded rail with DT350 rails and a traffic density up to 80 t.km gross/km per year. The most efficient upper structure track option is the one, which has the lowest value of unit costs per 1 t.km gross and covers the full life cycle of the railway track section operation.Discussion and conclusion. The developed methodological approaches will be used to evaluate, compare and select the most efficient upper structure track schemes under given operating conditions.